2002
DOI: 10.1007/s00542-002-0157-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro powder metallurgy for the replicative production of metallic microstructures

Abstract: Reproductive techniques like injection molding or embossing of feedstock provide microstructures of a wide variety of materials for a reasonable price to micro system technology. In this paper, the dependencies and barriers to produce high aspect ratio structures by micro metal injection molding are described; some results of embossing of metal powder based feedstocks are presented, too. The investigations show different influencing parameters for reaching high aspects ratios. The main factor is the used powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 1 publication
0
41
0
Order By: Relevance
“…After sintering, the shrinkage ranges 15%-22% and dimensional tolerance is about 0.005 [6,7] . Figure 2 shows the micro structures produced in Germany [8][9][10] . Additionally, researchers in IFAM found that microparts are easily welded together by co-sintering [11] , which will settle the ubiquitous problem of joining in MST.…”
Section: Research In Germanymentioning
confidence: 99%
“…After sintering, the shrinkage ranges 15%-22% and dimensional tolerance is about 0.005 [6,7] . Figure 2 shows the micro structures produced in Germany [8][9][10] . Additionally, researchers in IFAM found that microparts are easily welded together by co-sintering [11] , which will settle the ubiquitous problem of joining in MST.…”
Section: Research In Germanymentioning
confidence: 99%
“…To overcome these disadvantages, micrometal injection molding (MIM) has been established as a promising route to the mass production of metallic microcomponents (Merz et al, 2004;Tay et al, 2005;Liu et al, 2002). Micrometal injection molding (MIM) is the miniaturization of the conventional metal injection molding process (MIM) and it inherits the features of conventional MIM such as low production cost, geometric complexity, near net-shape, good tolerance and reproducibility (Rota et al, 2002). As in conventional MIM, the four major processing steps of MIM are formulation of the feedstock, molding to achieve design geometry, debinding to remove the binder and sintering to obtain desired properties.…”
Section: By Micromimmentioning
confidence: 99%
“…Micropowders of metals and ceramics have been used in injection molding or embossing [28][29][30]. The particles fuse together and form a continuous structure when they are sintered.…”
Section: Article In Pressmentioning
confidence: 99%